PENGARUH PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PEGAWAI - Kholidah, Nur; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This study aimed to examine the effect of the principles of good corporate governance, which is represented bythe openness, accountability, responsibility, independence and fairness of the performance of employees. Thedata used in this study are primary data in the form of a questionnaire with a sample taken 75 employees. Whilethe analytical technique used is multiple linear regression analysis. Based on the results of the feasibility testmodels known that the independent variables consisted of openness, accountability, responsibility, independenceand fairness has a significant influence on employee performance. Based on the next test by using t tests it isknown that all of the principles of Good Corporate Governance positive effect on employee performance, becausesome of the principles of good corporate governance can increase the openness of information on the companyregularly and timely and correctly, in addition the company established an audit committee to strengthen thefunction of internal oversight by the commissioner, the principle of accountability organize the fulfillment ofcorporate responsibility as a business entity in the community to all stakeholders, the principle of independencecan manage how employees are able to avoid the domination of unnatural by stakeholders, as well as theprinciples of fairness include clarity of the rights of shareholders to protecting the interests of shareholders,including the protection of minority shareholders of cheatingKeywords: openness, accountability, responsibility, independence, fairness, employee performance